DETERMINANT FACTORS THAT INFLUENCE ENTREPRENEURIAL INTENTION AMONG STUDENTS IN MALAYSIA - Lu Man Hong; Muhammad Azim Abu Hassan Sha'ari; Wan Farha Wan Zulkiffli; Roslizwati Che Aziz; Mohammad Ismail (Jurnal Manajemen dan Kewirausahaan, 2020)
The unemployment among university students become main issues in Malaysia since the increasing number of umnemployed graduates from higher education institution. In order to minimize this issue, entrepreneurship become one of the main solutions especially for higher education institution in Malaysia. This including the Kolej Islam Antarabangsa Sultan Ismail Petra (KIAS), Kelantan, Malaysia which provided entrepreneurship as main core subjects for their program of studies. Thus, this research tends to examine the factors that influence entrepreneurial intention among diploma student at Kolej Islam Antarabangsa Sultan Ismail Petra (KIAS) by using The Theory of Planned Behaviour (TPB). Quantitative research design has been where 100 set of questionnaires has been distributed to target respondents in order to get the necessary information. All data were panalyzed using SmartPLS software. The finding shows that attitude and entrepreneurial education are significant towards entrepreneurship intention. Therefore, this study is expected to provide a significant insight towards higher institutions, public as well as government about entrepreneurial intention.